2009
DOI: 10.1515/znc-2009-7-813
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Abiotic and Biotic Elicitors on Growth and Alkaloid Accumulation of Lycoris chinensis Seedlings

Abstract: Three-month-old seedlings of Lycoris chinensis were treated with biotic and abiotic elicitors: yeast elicitor (YE), methyl jasmonate (MJ), salicylic acid (SA), and sodium nitroprusside as NO donator (NO). We have shown that the addition of MJ and NO promotes the accumulation of galanthamine in these seedlings. The effect of these elicitors on the growth of the seedlings, as well as on the amount of the alkaloids accumulated in the seedlings was studied. The results showed that, in general, high doses of MJ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…MeJA treatment triggers the majority of secondary metabolites biosynthesis (i.e., terpenoids, phenylpropanoids, and alkaloids) through an extensive transcriptional reprogramming (Zhao et al, 2005; Pauwels et al, 2009; De Geyter et al, 2012; Misra et al, 2014). Previously, we also showed that exogenous MeJA application accelerated the Amaryllidaceae alkaloids accumulation in L. chinensis seedlings (Mu et al, 2009). Here, by using trancriptome sequencing, we investigated the MeJA-responsive transcriptional changes, and identified 4,165 DEGs (including 2,281 up-regulated and 1,884 down-regulated) between Con and MJ100 samples in L. aurea (Figure 5C).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…MeJA treatment triggers the majority of secondary metabolites biosynthesis (i.e., terpenoids, phenylpropanoids, and alkaloids) through an extensive transcriptional reprogramming (Zhao et al, 2005; Pauwels et al, 2009; De Geyter et al, 2012; Misra et al, 2014). Previously, we also showed that exogenous MeJA application accelerated the Amaryllidaceae alkaloids accumulation in L. chinensis seedlings (Mu et al, 2009). Here, by using trancriptome sequencing, we investigated the MeJA-responsive transcriptional changes, and identified 4,165 DEGs (including 2,281 up-regulated and 1,884 down-regulated) between Con and MJ100 samples in L. aurea (Figure 5C).…”
Section: Discussionmentioning
confidence: 70%
“…The elicitors derived from bacteria, fungi, viral pathogens and even plants also contribute to the variability in plant secondary metabolism (Berenbaum, 1995; Verma and Shukla, 2015). Previously, we showed that exogenous methyl jasmonate (MeJA) application accelerated the Amaryllidaceae alkaloids accumulation in Lycoris chinensis seedlings (Mu et al, 2009). In this study, by using elicitor MeJA treatment, the global expression patterns of genes involved in metabolism, particularly secondary metabolism, transcription factors, and transporter proteins were identified.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that in some plants of Amaryllidaceae family, the improved production of galanthamine was examined in MeJA-treated tissues and 1-aminocyclopropane-1-carboxylic acid (ACC)-treated somatic embryos respectively [65,66]. And in our previous study, we also found that the content of galanthamine in Lycoris chinensis and Lycoris radiata seedlings would have been affected after treating with sodium nitroprusside (SNP), salicylic acid (SA), or MeJA [67,68]. For the purpose of improving mRNA abundance of genes related to Amaryllidaceae alkaloids biosynthesis, the leaves were treated with those abiotic elicitors for RNA extraction.…”
Section: Cdna Synthesis and Normalizationmentioning
confidence: 84%
“…Only the percentage of DW referred to FW of the shoots treated with 100 µM MJ (11.4%) was significantly higher than that of the shoots growing in the other culture media, according to the two statistical tests applied. In two other amaryllidaceous plants, Narcissus confusus shoot‐clumps and Lycoris chinensis seedlings, high doses of MJ affected negatively their growth.…”
Section: Resultsmentioning
confidence: 99%
“…MJ elicitation of the Amaryllidaceae species Narcissus confusus (shoot‐clumps) and Lycoris chinensis (seedlings) successfully enhanced the production of GAL . However, to our knowledge, there are no references to the elicitation of alkaloid biosynthesis in in vitro cultures of L. aestivum .…”
Section: Introductionmentioning
confidence: 99%